Determining the Shortest Route for Eid Homecoming Route Using the Haversine Formula Method and A Star Algorithm - Nurpandi, Finsa; Syarifah Sany, Diny (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Eid homecoming, also known as